52.2k views
0 votes
12x - 3x + 90 = 12x + 57
X = ?

What is x ?

User Malcoauri
by
5.3k points

2 Answers

5 votes

Answer:

x = 11

General Formulas and Concepts:

Order of Operations: BPEMDAS

Explanation:

Step 1: Write equation

12x - 3x + 90 = 12x + 57

Step 2: Solve for x

  1. Combine like terms: 9x + 90 = 12x + 57
  2. Subtract 9 on both sides: 90 = 3x + 57
  3. Subtract 57 on both sides: 33 = 3x
  4. Divide 3 on both sides: 11 = x
  5. Rewrite: x = 11

Step 3: Check

Plug in x to verify it's a solution.

  1. Substitute: 12(11) - 3(11) + 90 = 12(11) + 57
  2. Multiply: 132 - 33 + 90 = 132 + 57
  3. Subtract: 99 + 90 = 132 + 57
  4. Add: 189 = 189
User Zulu
by
4.9k points
3 votes

Answer:

x = 11

Explanation:

12x - 3x + 90 = 12x + 57

simplify both sides

12x - 3x + 90 = 12x + 57

9x + 90 = 12x + 57

inverse operations

9x + 90 = 12x + 57

-9x -9x

90 = 3x + 57

-57 -57

33 = 3x

/3 /3

11 = x

User Oben Sonne
by
5.1k points